Clinical Impact of Pretreatment Human Immunodeficiency Virus Drug Resistance in People Initiating Nonnucleoside Reverse Transcriptase Inhibitor–Containing Antiretroviral Therapy: A Systematic Review and Meta-analysis. (17th November 2020) - Bertagnolio, Silvia; Hermans, Lucas; Jordan, Michael R; Avila-Rios, Santiago; Iwuji, Collins; Derache, Anne; Delaporte, Eric; Wensing, Annemarie; Aves, Theresa; Borhan, A S M; Leenus, Alvin; Parkin, Neil; et al.
Abstract: Background: Increased access to antiretroviral therapy (ART) has resulted in rising levels of pretreatment human immunodeficiency virus drug resistance (PDR). This is the first systematic review and meta-analysis to assess the impact of PDR on treatment outcomes among people initiating nonnucleoside reverse transcriptase inhibitor (NNRTI)–based ART, including the combination of efavirenz (EFV), tenofovir (TDF), and lamivudine or emtricitabine (XTC). Methods: We systematically reviewed studies and conference proceedings comparing treatment outcomes in populations initiating NNRTI-based ART with and without PDR. We conducted subgroup analyses by regimen: (1) NNRTIs + 2 nucleoside reverse transcriptase inhibitors (NRTIs), (2) EFV + 2 NRTIs, or (3) EFV/TDF/XTC; by population (children vs adults); and by definition of resistance (PDR vs NNRTI PDR). Results: Among 6197 studies screened, 32 were analyzed (31 441 patients). We found that individuals with PDR initiating NNRTIs across all the subgroups had increased risk of virological failure compared to those without PDR. Risk of acquisition of new resistance mutations and ART switch was also higher in people with PDR. Conclusions: This review shows poorer treatment outcomes in the presence of PDR, supporting the World Health Organization's recommendation to avoid using NNRTIs in countries where levels of PDR are high. Abstract : Higher risks of virological failure, acquisition of new resistance mutations, and treatment switch were observed among adults and children with pretreatment HIV drug resistance initiating nonnucleoside reverse transcriptase inhibitor–containing regimens, including efavirenz/tenofovir/lamivudine or emtricitabine.